Dampak Perubahan Kurikulum Terhadap Pembelajaran PAI Di SMA Negeri 1 Sangatta Utara - Zahrina Farizah Adiliani; Selawat Setiawan; Anjani Putri Belawati Pandiangan (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Education is the main factor in improving the quality of human resources and the progress of the nation. The curriculum as the core of education must be dynamic and innovative to respond to developments in science and technology. This research aims to understand the impact of curriculum changes on Islamic Religious Education (PAI) learning at SMA Negeri 1 Sangatta Utara. The research method used is descriptive qualitative, with interviews, observation and documentation as data collection techniques. The research results show that curriculum changes bring about 85% renewal of teaching materials, which include Aqidah, Akhlak, Qurdist, Ski and Fiqh, as well as adapting the material to the context of today's life. The P5 program in the Merdeka Curriculum increases students' creativity, motivation and learning experience even though it increases the teaching load. In conclusion, changes to the curriculum at SMA Negeri 1 Sangatta Utara support improving the quality of PAI education through the relevance of the material and developing students' skills according to the demands of the times.